Impact of admission glucose and 30-day major adverse cardiovascular events on patients with chest pain in an emergency setting: insights from the China EMPACT registry - Yin, Xinxin; Pan, Xin; Zhang, Jingyu; Wu, Shuo; Cui, Weikai; Wang, Yuting; Li, Chuanbao; Wang, Jiali; Chen, Yuguo (Frontiers in Cardiovascular Medicine, 2024)
Objective Although the association between admission glucose (AG) and major adverse cardiac events (MACE) is well-documented, its relationship with 30-day MACE in patients presenting with cardiac chest pain remains unclarified. In light of this, this study aims to examine the correlation between AG levels and the incidence of MACE in patients with chest pain in an emergency setting. Materials and methods We consecutively enrolled patients who presented to the emergency department for chest pain symptoms within 24 h from the EMPACT cohort in Eastern China (clinicaltrials.gov, Identifier: NCT02536677). The primary outcome was 30-day MACE, including all-cause death, recurrent myocardial infarction, urgent target vessel revascularization, stroke, cardiogenic shock, and cardiac arrest (CA). The associations of AG levels with 30-day MACE were analyzed using Kaplan–Meier analysis and Cox regression models. Results Among 1,705 patients who were included in this study, 154 (9.03%) patients met the primary outcome at 30 days. The average age of the patients was 65.23 ± 12.66 years, with 1,028 (60.29%) being male and 500 (29.33%) having diabetes. The median AG levels were 7.60 mmol/L (interquartile range: 6.30–10.20). Kaplan–Meier survival analysis revealed significant differences in the 30-day MACE risk (P < 0.001 according to the log-rank test). We found that the highest AG level (Q4) was associated with increased MACE risk compared with the lowest AG level [adjusted hazard radio (aHR): 2.14; 95% confidence interval (CI): 1.2–3.815; P = 0.010]. In addition, Q4 level was also associated with increased all-cause death risk (aHR: 3.825; 95% CI: 1.613–9.07; P = 0.002) and increased CA risk (aHR: 3.14; 95% CI: 1.251–7.884; P = 0.015). Conclusions An elevated AG level significantly correlates with a higher incidence of 30-day MACE in patients with acute chest pain. The findings reveal the importance of managing AG levels to potentially reduce the risk of adverse cardiac events.